1986
DOI: 10.1111/j.1600-0609.1986.tb02275.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical detection of normal and abnormal megakaryocytes using monoclonal antibody to glycoprotein IIb‐IIIa (TP80): The quantitative assay in normal and in leukaemic patients

Abstract: We identified bone marrow megakaryocytes by an immunocytochemical technique using a monoclonal antibody (TP80) against platelet glycoprotein IIb‐IIIa (GPIIb‐IIIa). The immunocytochemical technique using TP80, specific to megakaryocytes, enabled us to observe cellular morphology and immunological reaction under light microscopy, and permitted quantitative assessment of megakaryocytes. In normal marrow, TP80 labelled 22 ± 5 megakaryocytes / 104 mononuclear cells (mean ± 1 SD, n = 14). In addition to typical larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Therefore, it is suggested that not only type 1 but also type 3 atypical MKs are of diagnostic significance in MDS. However the particular dysplastic changes affecting the MK lineage which are specific for and of diagnostic value in MDS should be assessed further, because previous investigators have reported the detection of minor population of atypical MKs, corresponding to type 1 or 3 atypical MKs in normal marrows (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is suggested that not only type 1 but also type 3 atypical MKs are of diagnostic significance in MDS. However the particular dysplastic changes affecting the MK lineage which are specific for and of diagnostic value in MDS should be assessed further, because previous investigators have reported the detection of minor population of atypical MKs, corresponding to type 1 or 3 atypical MKs in normal marrows (15,16).…”
Section: Discussionmentioning
confidence: 99%